2004
DOI: 10.1088/0741-3335/46/12b/033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma processing techniques for tritium inventory control in fusion research

Abstract: Some techniques with a long tradition in the plasma technology field have already been successfully applied to research in plasma-wall interactions of fusion devices. They have produced important advances in the control of particle and energy exhaust. In this paper, the possible application of these techniques to the problem of tritium inventory control in fusion reactors with carbon-based plasma facing materials, as in ITER, is proposed. It is based on a critical analysis of relevant information obtained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…However, the conductance of a 2mm hole in molecular regime for acetylene is ∼0.36 ls -1 . This value is in very good agreement with the calibration factor for acetylene under low pressures, given by Equation 5.…”
Section: Methane/nitrogen/hydrogen Plasmasupporting
confidence: 86%
See 2 more Smart Citations
“…However, the conductance of a 2mm hole in molecular regime for acetylene is ∼0.36 ls -1 . This value is in very good agreement with the calibration factor for acetylene under low pressures, given by Equation 5.…”
Section: Methane/nitrogen/hydrogen Plasmasupporting
confidence: 86%
“…Again, a plasma was initiated over the fresh carbonized walls, but this time methane was removed from the gas phase and only a N 2 /H 2 (20:80) mixture was used. This kind of plasma has been recently proposed for the removal of carbon contaminants in fusion devices [5] due to the lack of oxygen in their composition (highly efficient for the task but with deleterious side effects on the rest of the components) and their high etching rate. Separate experiments have yielded erosion rates up to 3.6 nm min -1 of laboratory-produced, hard a-C:H films.…”
Section: Nitrogen/hydrogen Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary laboratory experiments on plasmaassisted deposition of amorphous hydrocarbon (a-C:H) films in rf and dc low-pressure plasmas by Mutsukura [2], Vandentop et al [3], and Tabares et al [1] have reported on considerable reduction of film growth from methane plasmas if NO or N 2 are admixed to the gas phase. It has been hypothesized that this is due to the scavenging effect of N 2 and NO [1,[4][5][6]. Scavenger particles are supposed to transform reactive species into non-reactive ones, thereby reducing the deposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature different diagnostics were applied to study the interaction between nitrogen and hydrogen containing mixtures. In fact, one can find a lot of information for totally different experimental conditions: catalyser based HCN production at atmospheric pressure [3] , production of synthetic materials and gas phase reactions in microwave plasmas [4,5], low temperature plasma studies [6,7,12,13] as well as experiments in fusion experiments [8]. The spectrum of intermediate species and final products covers nearly all possibilities for C x H y N z (for x = 1,2,.. y =1…6 , z =1,2).…”
Section: Introductionmentioning
confidence: 99%